CONTESTATION OF THE EFFICIENCY AND EFFECTIVENESS PRINCIPLES ON THE LOCAL REGULATIONS TOWARD THE COMMUNITY PROTECTION - Muammar Arafat Yusmad (Jurnal Dinamika Hukum, 2018)
The sustainable national law development is expected to guarantee people’s need on the legislation which protects the community. Local Regulation (Perda) has a strategic position as an instrument of the regional autonomy implementation in terms of national development decentralization. The Re-gional regulation formulation must observe the principles of good legislation including the principle of efficiency and effectiveness. The research focuses on the form of contestation between the principles of efficiency and effectiveness on a Regional regulation for community protection. The problems are analyzed by applying the theory of law enactment. From the analysis, it shows that the legal arguments include: The occurrence of contestation between the principles of efficiency and effectiveness on the Perda enactment is caused by the absence of community protection as stated in Regional regulation; The principles contestation in Perda results in conflict between legal norms and legislation. Keywords:  efficiency and effectiveness, contestation, protection